Estimasi Cadangan Minyak pada Lapangan Trad Layer X Tank 2 Reservoir Deltaic - Maria Cindy Manik; Stevan Vincent Djongihi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Structure MY was first drilled in late 1965 and reached its peak oil production in April 1966, with Np of 12.12 MMSTB, which continued until May 2013. At present, efforts to reactivate mature wells are being intensified in order to increase national production. However, a field can be declared economically feasible for production enhancement if it possesses sufficient oil reserves. Therefore, reserve estimation becomes a crucial step in field evaluation. In this study, reserve estimation was carried out using the Material Balance Method with the assistance of the MBAL simulator. This method is used to determine the magnitude of reserves in developed field reservoirs by utilizing parameters such as PVT data, tank data, production data, and field historical data. The calculation results indicate that the dynamic estimate obtained using the MBAL software is 18.22 MMSTB, with a percentage difference of 1.6% from the static OOIP calculation, and the drive mechanism operating in Layer X is a combination of water influx and fluid expansion.